Aesthetics and corporate identity. - Villamizar Duarte, Eduardo A.; Osorio Contreras, Jesús Alejandro (AiBi Journal of Research, Administration and Engineering, 2014)
Aesthetics is the science that deals with the problem of feeling to make a philosophical reflection on the nature of what is beautiful about artistic Visual and audiovisual products. Business and advertising, communication-oriented conceiving their supports as artistic products from its inclusion in this field in the year of 1908 in Berlin Germany and driven in a visionary manner by the Rathenau brothers, creators of the AEG company, materialized by the action of the architect, designer and German graphic artist, Peter Behrens and the Austrian sociologist, Otto Neurathwho were responsible for the change and creation of the style graphic of the visual identity of this firm, constituting an act pioneer in the use of aesthetics within the corporate branding. Thus was invented the concept and practice of corporate identity, providing a new way in business communication, Act emulated by other recognized brands, who have spoken their signs and vectors of communication, to strengthen them with aesthetic values, making them better able to compete in environments affected by new technologies that have been created for new brands and dynamic ways to build links communicate an aesthetic itself, full of attributes that shocks and is transmitted through social networks, adapting to the changes of the environment and the consumer, trend to which enterprises of the region for the sake of their positioning and competitiveness must be entered.